Multidetector Computed Tomography Evaluation of Anomalies of Aortic Arch Branching (Academia Journal of Medicine, 2020)
Background: Anatomic variations in the branching pattern of the aortic arch is known for a long time. Advances in modern medicine have led to an increasing number of endovascular and vascular reconstructive procedures where the pre-procedural information about these variations is extremely important. Besides, these variations may serve as a marker of thoracic aortic disease. Hence, we tried to evaluate the incidence of these anatomic variations in the branching of the aortic arch utilizing routine contrast-enhanced computed tomography of the thorax (CECT-Th) rather than aortograms. The aims and objectives is to the main aim of the study was to evaluate the role of multidetector routine CECT-Th in the detection of anomalies of branching of the aortic arch along with an estimation of their incidences. Subjects & Methods: Three-hundred and fifty CECT-Th examinations were included in our study over some time with the exclusion of 27 examinations. The type of aortic arch branching pattern was noted, and their incidence was calculated. Results: Majority of the patients in our study were in 41-60yrs age group with male predominance. Majority of the patients had three branches arising from the arch of aorta. The commonest variant was bovine type (14.2%) where the left common carotid arises from the right brachiocephalic artery followed by the isolated vertebral artery and aberrant right subclavian artery in the decreasing order of frequency. Conclusion: Anomalies of branching of aortic arch can be optimally detected on routine CECT-Th examinations performed on a multidetector CT scanner. Anomalies are seen in nearly one-fifth to one-quarter of subjects with the bovine type being the commonest and aberrant right subclavian artery being the rarest.
Keywords: Multidetector Computed Tomography; Anomalies; Aortic Arch